Kebijakan Perlindungan Sosial di Indonesia: Analisis Perbandingan Perlindungan Sosial di Masa Pandemi Covid-19 dan Universal Basic Income (UBI) - Nanda Rizka Syafriani Nasution; Heri Kusmanto; Tony P. Situmorang (PERSPEKTIF, 2023)
This study aims to compare social protection policies in Indonesia during the Covid-19 pandemic with Universal Basic Income (UBI) as a new paradigm of social protection policies in Indonesia. This research is a research using literature study method or literature review. In essence, a literature review is a thorough review of previous research on a particular topic. Literature studies can be obtained from various sources, including journals, books, documentation, the internet and libraries. The literature study method collects library data, reads and takes notes, and manages writing materials. The type of writing used is a literature study that focuses on writing results related to writing topics or variables. The results of the study show that in the Indonesian context, although UBI can minimize the level of targeting errors, both inclusion error (including households that are not poor in targeting) and excluding poor households in targeting, the benefits received by disadvantaged groups can be higher than assistance programs. with specific targets. In addition, it should be noted, the application of UBI in times of crisis and economic recovery must still be complemented by social assistance programs with specific targets.